Synthesis and characterization of Pt/Fe?Zr catalysts for the CO selective oxidation - Schmal, Martin (2010)
Catalysts of Pt on Fe2O3 and mixed oxides FexZr(1−x)O2 were prepared for the selective CO + H2 oxidation. X-ray diffraction and Mössbauer spectroscopy showed -Fe2O3 in pure support, a solid solution for x = 0.25 and mixed oxides with segregated phases for higher “x” values. Mössbauer results showed also that with increasing the Zr content Zr4+ ions substitute the Fe3+ ions in the -Fe2O3 lattice, and also Fe3+ ions diffusing into the zirconia lattice. The Pt/Fe0.25Zr0.75O2(p) exhibited only Fe3+ inside the ZrO2 lattice. After reduction, Fe3O4 was found in the catalysts, which decreased with increasing zirconium loading. It is interesting to note that the corresponding precursor presents 83% of Fe3+ located in the ZrO2 lattice and the remaining 17% corresponds to hematite. Catalytic tests for the preferential oxidation of CO containing H2 showed maximum CO conversion at different temperatures after reaching total oxygen conversion. The CO conversion decreased with increasing iron content in the mixed oxide. The Pt/Fe2O3 catalyst is the most active compared to the other Pt/mixed oxide and Pt/ZrO2. Results showed the following order: Pt/Fe2O3(c) > Pt/Fe0.75Zr0.25O2(c) > Pt/Fe0.25Zr0.75O2(c) > Pt/ZrO2. The Pt/Fe0.25Zr0.75O2(c) presented high selectivity (56%) at 90 ◦C and is 2-fold higher compared to the Pt/Fe2O3 and Pt/ZrO2 catalyst.